The Immune Profile of the Endometrium in the "Uterine Factor" of Infertility - Miroslava L. Polina; Victor E. Radzinsky; Ludmila M. Mikhaleva; Irina I. Vityazeva; Marina B. Khamoshina; Sergey А. Mikhalev; Natalya I. Douglas (International Journal of Biomedicine, 2023)
Background: This study aimed to investigate the endometrial characteristics (pathomorphological and immunological) of women with infertility. Methods and Results: Data from an immunohistochemical study of endometrial biopsies (TNF-α, IL-10, GM-CSF, CXCL16, BCA1, TGF-β1) collected during the “implantation window” and microbiota studied by real-time polymerase chain reaction in 171 patients (21 women with unexplained infertility, 36 - chronic endometritis, 74 - tubal-peritoneal infertility, 22 - external genital endometriosis, 8 - "thin" endometrium, and 10 healthy fertile women from the comparison group) were analyzed to identify molecular signatures. Chronic endometritis was verified morphologically and immunohistochemically. Each group revealed different immune endometrial phenotypes. The basis of the "normal" phenotype was a controlled immune inflammation and a Lactobacillus-dominant microbiota (LDM) type. In contrast to the comparison group, in the group with the phenotype of chronic inflammation, an excessive immune response (overexpression of TNF-α, GM-CSF, CXCL16, BCA1, and a decrease in IL-10 and TGF-β1 in glandular epithelium and stroma) was determined on the background of non-Lactobacillus-dominated microbiota (NLDM) type (63.3%) (P<0.001). The peculiar feature of a dysplastic phenotype was a "poor" immune response, with maximal TGF-β1 overexpression (P<0.001) and a NLDM type (47.1%). We determined an excessive immune response in the proliferative endometrial phenotype (GM-CSF overexpression by 1.2 times in the glandular epithelium and stroma [P<0.001 in both cases] and a decrease in IL-10 by 1.6 times in the glandular epithelium and 1.2 times in the stroma [P<0.001 in both cases]). Uterine microbiome disorders were detected less frequently than in patients with the inflammation phenotype (31.6%) (P=0.01). In the phenotype with impaired immune status, there was a decrease in GM-CSF, BCA1, CXCL16, TNF-α, and IL-10 markers in both endometrial compartments (P<0.001) with a LDM type (81.2%). Conclusion. The molecular signatures of the endometrium are due to the heterogeneity of immune factors and microbiota. Aberrant expression of immune factors may contribute to the formation of a microenvironment unfavorable for blastocyst implantation.